Analisis Pengaruh Penerapan Corporate Governance Terhadap Integrated Reporting - Thisya Audina; Agrianti Komalasari; Rona Majidah (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
This study aims to analyze the effect of Corporate Governance on Integrated Reporting (IR) in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Corporate Governance is measured using three indicators: Corporate Governance Perception Index (CGPI) score, the number of board of directors, and the number of audit committee members. Integrated Reporting is assessed based on the seven elements recommended by the International Integrated Reporting Council (IIRC). The sample was selected using purposive sampling, resulting in 55 SOEs. The data were analyzed using multiple linear regression with the aid of SPSS. The results show that CGPI and the board of directors have a positive and significant effect on Integrated Reporting, while the audit committee has no significant effect. These findings support agency theory, indicating that strong corporate governance plays an essential role in promoting transparency and accountability in reporting. The study implies the need to strengthen governance structures and encourages regulators to consider adopting IR as a future reporting standard.